If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(7k + -4) = 24 Reorder the terms: -9(-4 + 7k) = 24 (-4 * -9 + 7k * -9) = 24 (36 + -63k) = 24 Solving 36 + -63k = 24 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -63k = 24 + -36 Combine like terms: 36 + -36 = 0 0 + -63k = 24 + -36 -63k = 24 + -36 Combine like terms: 24 + -36 = -12 -63k = -12 Divide each side by '-63'. k = 0.1904761905 Simplifying k = 0.1904761905
| x-37=.5x+.5 | | 4(5x+7-8)+2=-18 | | 21-7m=2 | | x^(3/4)*x^(5/4) | | 4/9y-1/3=1/7 | | 3.01x^2+12.12x-22.98=0 | | 6k^2+5k-7=0 | | -4(2-7r)=-31+5r | | 252/45 | | 93*84= | | 9/7x-1/x | | 4(5x+7-8)+2=-8 | | 9(8+2r)=35 | | 2(x-a)+3y=3x+a | | 2x-(3-x)=8 | | -7-11(-9p+9)=-7p-3(1-p) | | x/3-2=18 | | -2(z-3)=10 | | 5+2(x-4)=2[5-6(x+2)] | | x+0.05x=169 | | -35x=-35 | | x^3/4*x^5/4 | | .4x-1=.7x+1.5 | | 31=22z-15+-28 | | 5x+8=13+7(x-3) | | 3n+5=2n+9 | | -7(3x+8)=-21x-56 | | 5x^3y-15x^2y+10xy= | | 2(1+2x)-3=4-(4-3x) | | 3(-2-4x)=42 | | 7x+19=-2x+5 | | 4-6m+5m=7 |